TINGKAT KEAKTIFAN SISWA KELAS V SDI BANGKAKELI DALAM MENGERJAKAN TUGAS RUMAH DI TENGAH PANDEMI COVID-19 - Stefanus Divan (JURNAL PENDIDIKAN DASAR, 2021)
This enquiry intends to designate partaking altitude of grade v students of Bangkakeli public elementary school in doing their homework throughout caovid-19 pandemic, the cause factor of low students’ altitude in finishing homework, and the endeavor of teacher in lifting up student’s altitude in competing homework in the midst of covid-19 pandemic. The used method in this research is descriptive qualitative. The subject in this enquiry is grade V teacher, principal, students, and the parents. Data collecting technique used an interview, observation, and documentation. The fallout of this enquiry pointed out that altitude partaking of students in completing homework throughout pandemic considered low. The cause factor of students’ low partaking is internal factor and external factor. The endeavor of teachers in developing students partaking in finishing homework in the midst of covid-19 pandemic is maximizing portfolio learning model, communication maximizing and corporate with the parents of students.